Design of physical education teaching in colleges and universities based on emotional education under the environment of internet sharing information - Hou, Wentao; Li, Long; Xing, Shuying (Frontiers in Psychology, 2022)
In teaching, through the emotional education of students, the distance between teachers and students can be shortened, and the connection between teachers and students can be enhanced, promoting mutual understanding. In traditional teaching, there is a lack of emotional education for students. Therefore, from the perspective of emotional education, this paper discussed the function of emotional education in college physical education and a series of measures to implement it. Its application in college physical education were also discussed and analyzed, in order to improve the comprehensive quality of college students and the quality of college physical education. This can also serve as a benchmark for college physical education instructors' level of training, helping to build a solid basis for the advancement of education. Through the comparison of emotional education in the environment of sharing information on the Internet and traditional education, the main points of comparison were the timeliness of communication, the integrity of emotional education, the relationship between teachers and students, and the quality of teaching. The results found that the timeliness of communication has increased by 9.3%, and the integrity of education has increased by 30%. The relationship between teachers and students has also improved significantly. In terms of teaching quality, students were more satisfied, and the teaching quality was improved. It showed that emotional education in the environment of sharing information on the Internet can better help students improve their learning situation, enhance their learning effect, and learn better in happiness.